Perbaikan Proses Pengujian Qualitas Pada Produk Donut Mix Untuk Meningkatkan Produktivitas - Fatma, Nur Fadilah; Ponda, Henri; Yuliani, Dian (Program Studi Teknik Industri Universitas Muhammadiyah Tangerang, 2021)
A company, will experience a process of ups and downs where this is a common thing. At the end of 2020, the world was shocked by the corona virus pandemic in all parts of the world. The impact of this pandemic has led to the confinement of employees as in this company. So that it makes productivity decrease, especially in the Quality department. To deal with this, the company asks employees to make changes in the sample testing flow process, to identify non-value-added activities. This resulted in disruption of the shipping process and many samples piled up. The purpose of this study is to identify and plan improvements that lead to non-value-added activities. This study uses the Fault Tree Analysis (FTA) and 5W1H methods. The FTA analysis shows that the cause of non-value-added activity is the mixing process is too long, too many processes during molding and the proofing process is too long. Based on this FTA analysis, priorities for corrective action plans can be determined to implement these improvements. The improvement plan uses the 5W1H method, which is to review the current test methods. The results of this study were very effective because they were able to reduce the processing time by 59 minutes.Keywords: Fault Tree Analysis, 5W1H, flow process, effectiveness and pandemic.